APLIKASI TERAPI ‘GUIDED IMAGERY’ UNTUK PASIEN ASMA DENGAN STATUS ASMATIKUS PADA UNIT GAWAT DARURAT - Nurma Afiani (LPPMK STIKES Widyagama Husada, 2013)
Asthma is a disease of the respiratory tract that can be caused by multifactor. Psychological stress may be one trigger of asthma attacks. One of the psychological therapies that can be performed on patients with asthma is guided imagery. The method used in this study is a literature review as a basis for research to be conducted. The study of literature shows that there is a positive effect of guided imagery therapy against one of the lung function parameters forced expiratory lung capacity (force expiratory volume / FEV). Complementary therapies guided imagery is in line with medical treatment by other health care team to achieve optimal patient conditions